Signaling pathways and molecular mechanisms involved in the onset and progression of cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL); a focus on Notch3 signaling - Parasta Heidari; Motahareh Taghizadeh; Omid Vakili (The Journal of Headache and Pain)
Abstract Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an autosomal-dominantly inherited cerebral small-vessel disease (SVD). CADASIL has diverse clinical features such as migraine with aura, dementia, and recurrent strokes, and is caused by a pathogenic mutation in the NOTCH3 gene which encodes a transmembrane receptor found in smooth muscle cells of small arteries and pericytes of brain capillaries. Pathogenic mutations alter the number of cysteine residues in the extracellular domain of NOTCH3, leading to the abnormal accumulation of granular osmiophilic material in the vessels of affected individuals. In addition, potential signaling pathways, such as transforming growth factor beta (TGF-β), may be involved in pathogenesis of the disease. This review aims to elucidate these mechanisms, particularly NOTCH3, in the context of CADASIL pathogenesis, providing insight into the role of NOTCH3 signaling and discussing the significance of these pathways for potential future therapeutic interventions in CADASIL patients.